Bioceramic materials with ion‐mediated multifunctionality for wound healing. Issue 1 (27th December 2022) - Wang, Xiaocheng; Tang, Min
Abstract: Regeneration of both anatomic and functional integrity of the skin tissues after injury represents a huge challenge considering the sophisticated healing process and variability of specific wounds. In the past decades, numerous efforts have been made to construct bioceramic‐based wound dressing materials with ion‐mediated multifunctionality for facilitating the healing process. In this review, the state‐of‐the‐art progress on bioceramic materials with ion‐mediated bioactivity for wound healing is summarized. Followed by a brief discussion on the bioceramic materials with ion‐mediated biological activities, the emerging bioceramic‐based materials are highlighted for wound healing applications owing to their ion‐mediated bioactivities, including anti‐infection function, angiogenic activity, improved skin appendage regeneration, antitumor effect, and so on. Finally, concluding remarks and future perspectives of bioceramic‐based wound dressing materials for clinical practice are briefly discussed. Abstract : In this review, we provide a brief summary of the state‐of‐the‐art progress on bioceramic materials with ion‐mediated bioactivity for wound healing applications. The emerging bioceramic‐based materials for wound healing are highlighted based on their ion‐mediated bioactivities, including enhanced angiogenesis, antibacterial activity, improved skin appendage regeneration, anti‐tumor effects, wound monitoring, and other multi‐functions.